2017
DOI: 10.1088/1361-6579/aa52b3
|View full text |Cite
|
Sign up to set email alerts
|

Consecutive ultra-short-term heart rate variability to track dynamic changes in autonomic nervous system during and after exercise

Abstract: Compared with the indices in frequency domain, the Poincaré indices were more sensitive and accurate in UST measurement of ANS during exercise. The results demonstrated that the UST method could characterize the dynamic changing tendency of ANS during and after exercise and quantify the differences of changes in ANS induced by exercise with different intensities. In particular, the vagal branch functioned dominantly in controlling HR in S0 but the effect of the sympathetic branch on HR enhanced with the increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…When the skeletal muscle is moving, the autonomic nervous system will regulate the functions of the cardiovascular system to satisfy the energy and metabolism demands. Moreover, the control of the autonomic nervous system over HR is a dynamic regulation process (Fisher, Young & Fadel, 2015;Dong, 2016;Chen et al, 2017). Much previous research has also indicated a close linear correlation between HR and VO 2 which is why changes in HR can be used to evaluate exercise intensity (Strath et al 2001;Bouchard & Trudeau 2008;Villars et al 2012;Domene & Easton, 2014;Rousset et al 2015;Colosio et al, 2018).…”
Section: Discussionmentioning
confidence: 98%
“…When the skeletal muscle is moving, the autonomic nervous system will regulate the functions of the cardiovascular system to satisfy the energy and metabolism demands. Moreover, the control of the autonomic nervous system over HR is a dynamic regulation process (Fisher, Young & Fadel, 2015;Dong, 2016;Chen et al, 2017). Much previous research has also indicated a close linear correlation between HR and VO 2 which is why changes in HR can be used to evaluate exercise intensity (Strath et al 2001;Bouchard & Trudeau 2008;Villars et al 2012;Domene & Easton, 2014;Rousset et al 2015;Colosio et al, 2018).…”
Section: Discussionmentioning
confidence: 98%
“…It can be seen that athletes have more considerable energy expenditure than the sedentary participants during exercise. During movement, to meet the metabolic requirements of skeletal muscles, the autonomic nervous system controls the heart rates and expansion of blood vessels through a complex dynamic process ( Fisher, Young & Fadel, 2015 ; Dong, 2016 ; Chen et al., 2017 ). In line with a large number of studies in recent years, VO 2 and HR are closely related, and there is a linear correlation between them.…”
Section: Discussionmentioning
confidence: 99%
“…When the skeletal muscle is moving, the autonomic nervous system will regulate the functions of the cardiovascular system to satisfy the energy and metabolism demands. Moreover, the control of the autonomic nervous system over HR is a dynamic regulation process (Fisher, Young & Fadel, 2015; Dong, 2016; Chen et al., 2017). Much previous research has also indicated a close linear correlation between HR and VO 2 which is why changes in HR can be used to evaluate exercise intensity (Strath et al., 2001; Bouchard & Trudeau, 2008; Villars et al., 2012; Domene & Easton, 2014; Rousset et al., 2015; Colosio et al., 2018).…”
Section: Discussionmentioning
confidence: 99%